The Rearing of Clown Loach (Chromobotia macracanthus) Larvae by Using Enriched Live Foods - Chumaidi, .; Nurhidayat, .; Priyadi, A. (Jurnal Akuakultur Indonesia, 2009)
The enrichment of natural live  food with unsaturated fatty acid can increase survival and growth rate of fish larvae. The purpose of  this experiment was to know the effect of various natural live food with or without nutrient enrichment on survival and growth rate of clown loach (Chromobotia macracanthus) larvae.  The experiment was done indoor by using plastic jars filled 5 L water and aerated continuously.  Twenty clown loach larvae of four days old, 5.58 ± 0.12   mm in average length,  were stocked in plastic jars and  were reared for 28 days. The treatment were: a) Artemia nauplii as control;  b) rotifer without enrichment;  c) enriched rotifer, d) Moina nauplii without enrichment, and e) enriched Moina nauplii.  As enrichment agent, we used 200 mg of tuna eggs powder and 200 mg of baker's yeast which dissolved and  aerated in 2 L of water for one hour.  Proximate analysis for amino  and fatty acids content were done before the treatment, at 5 days old and at 32 days old (juvenile).  The result showed that higher survival (80.00%) and growth rate (average body length 12.80±1.85 mm) could be achieved by feeding clown loach larvae with enriched Moina nauplii. Keywords: clown loach larvae,  live feed, nutrient enrichment   ABSTRAK Pengkayaan asam lemak tak jenuh dari pakan hidup dapat meningkatkan sintasan dan pertumbuhan larva ikan.  Penelitian dilakukan bertujuan untuk mengetahui pengaruh pakan hidup dengan atau  tanpa diperkaya nutrisinya terhadap sintasan dan pertumbuhan larva ikan botia (Chromobotia macracanthus).  Penelitian dilaksanakan di dalam ruangan tertutup menggunakan wadah plastik yang berisi media air 5 L serta diaerasi terus menerus.  Larva umur empat hari dengan panjang rata-rata 5,58 ± 0,12 mm ditebar sebanyak 20 ekor per wadah.  Pemeliharaan larva dilakukan selama 28 hari. Perlakuan perbedaan jenis pakan hidup dengan atau tanpa diperkaya, yaitu : a) naplii Artemia (kontrol), b) rotifer tanpa diperkaya nutrisinya, c) rotifer diperkaya nutrisinya, d) nauplii Moina tanpa diperkaya nutrisinya dan e) nauplii Moina diperkaya nutrisinya.  Pengkayaan pakan alami menggunakan tepung telur tuna dan ragi roti masing-masing 200 mg dalam 2 L media air yang diaerasi selama 1 jam. Analisis proksimat, asam amino dan asam lemak pakan alami  dan larva umur empat hari dilakukan sebelum penelitian dan juvenil botia 32 hari dianalisis pula.  Hasil penelitian menunjukkan bahwa sintasan (80,00%) dan pertumbuhan (panjang mutlak 12,90 ± 1,85 mm) yang tinggi dapat diperoleh dengan memberikan nauplii Moina yang diperkaya pada larva botia Kata kunci: larva ikan botia, pakan alami, pengkayaan nutrisi